Monocytic MDSC mobilization promotes tumor recurrence after liver transplantation via CXCL10/TLR4/MMP14 signaling - Hui Liu (Cell Death and Disease, 2021)
Abstract Tumor recurrence is the major obstacle for pushing the envelope of liver transplantation for hepatocellular carcinoma (HCC) patients. The inflammatory cascades activated by acute liver graft injury promote tumor recurrence. We aimed to explore the role and mechanism of myeloid-derived suppressor cell (MDSC) mobilization induced by liver graft injury on tumor recurrence. By analyzing 331 HCC patients who received liver transplantation, the patients with graft weight ratio (GWR, the weight of liver graft divided by the estimated standard liver weight of recipient) <60% had higher tumor recurrence than GWR ≥60% ones. MDSCs and CXCL10/TLR4 levels were significantly increased in patients with GWR <60% or tumor recurrence. These findings were further validated in our rat orthotopic liver transplantation model. In CXCL10 −/− and TLR4 −/− mice of hepatic ischemia/reperfusion injury plus major hepatectomy (IRH) model, monocytic MDSCs, instead of granulocytic MDSCs, were significantly decreased. Importantly, CXCL10 deficiency reduced the accumulation of TLR4+ monocytic MDSCs, and CXCL10 increased MDSC mobilization in the presence of TLR4. Moreover, MMP14 was identified as the key molecule bridging CXCL10/TLR4 signaling and MDSC mobilization. Knockout or inhibition of CXCL10/TLR4 signaling significantly reduced the tumor growth with decreased monocytic MDSCs and MMP14 in the mouse tumor recurrent model. Our data indicated that monocytic MDSCs were mobilized and recruited to liver graft during acute phase injury, and to promote HCC recurrence after transplantation. Targeting MDSC mobilization via CXCL10/TLR4/MMP14 signaling may represent the therapeutic potential in decreasing post-transplant liver tumor recurrence.